Pengaruh Akun Media Sosial Instagram @whiteboardjournal Terhadap Pemenuhan Kebutuhan Informasi Pembaca - Khansa, Shazrin Daniyah; Putri, K. Y.S. (School of Communication - Atma Jaya Catholic University of Indonesia, 2021)
As time develops, so has globalization. The field of communication and technology is one of the fields that is developing rapidly due to the development of globalization. One of the effects is social media. In this era, social media can be easily used by all people. Various social media provide various information on various platforms so that people can choose according to their information needs. The most frequently used social media in Indonesia is Instagram. Nowadays, Instagram is not only used for individual needs, but now Instagram has many benefits, for example, to do buying and selling or online shop, and to spread the latest information or news. Therefore, the purpose of this study is to find out how the influence of the Instagram @whiteboardjournal social media account on meeting the information needs of readers. This study uses a quantitative approach with a survey method. The population of this research is Communication Science students class of 2019 State University of Jakarta totaling 82 people with a total sample of 68 people. From the results of the study, it can be seen that there is an influence between the Instagram social media account @whiteboardjournal with meeting the information needs of readers.